Event marketing : how to successfully promote events, festivals, conventions, and expositions - Preston, Chris, 1961- (John Wiley & Sons, 2012)
A modern, completely updated guide to effective event marketing As the events market becomes increasingly saturated, it is essential for a successful event professional to understand the use of strategic marketing plans. Events are everywhere & mdash;in the U.S. alone, there are more than 2,500 music festivals a year, for example, while the UK hosts over 70 different beer festivals each year. In such a crowded market, how can the event planner ensure that his or her event stands out? Marketing expert Chris Preston has the answers in this second edition of Event Marketing. From the basics of prom.